A BUSINESS INTELLIGENCE STRUCTURAL EQUATION MODEL ON MEASURING THE RELATIONSHIP BETWEEN CUSTOMER INTELLIGENCE, MARKETING INTELLIGENCE, AND EMPLOYEE INTELLIGENCE, AND ITS EFFECT ON OPERATIONAL PERFORMANCE OF ORGANISATION - N, Geetha; U M, Gopal Krishna (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Integration of enterprise applications in real-time represents a new data management challenge for businesses with a large number of direct customers. This challenge arises as a result of the proliferation of channel-oriented applications, such as e-commerce support and call center support, among other examples. A growing number of companies are implementing Business Intelligence (BI) systems and tools in order to gain insight from the past and make accurate projections about the future. Companies have realised the importance of utilising business intelligence concepts like Customer Intelligence, Marketing Intelligence, and Employee Intelligence to ensure the achievement of the objectives outlined in their business strategies. Examining the business requirements provides insights into the role and necessity of real-time BI. The paper investigates the “relationship between the customer intelligence, marketing intelligence, employee intelligence and its impact on operational performance”.